2021
DOI: 10.3390/pr9061027
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Industrial Process Fault Diagnosis Based on Time Delayed Mutual Information Analysis

Abstract: Causal relations among variables may change significantly due to different control strategies and fault types. Off line-based knowledge is not adequate for fault diagnosis, and existing causal models obtained from data driven methods are mostly based on historical data only. However, variable correlation would not remain identical, and could be very different under certain industrial operation conditions. To deal with this problem, a fault diagnosis framework is proposed based on information solely extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…This leads to manipulation of the valve position to prevent the fault from cascading any further. From the fault path, X51 was correctly identified as the root cause variable, and this is in agreement with fault description in the literature . The causal map obtained using the Gaussian estimator is shown in Figure a.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This leads to manipulation of the valve position to prevent the fault from cascading any further. From the fault path, X51 was correctly identified as the root cause variable, and this is in agreement with fault description in the literature . The causal map obtained using the Gaussian estimator is shown in Figure a.…”
Section: Resultssupporting
confidence: 85%
“…From the fault path, X51 was correctly identified as the root cause variable, and this is in agreement with fault description in the literature. 45 The causal map obtained using the Gaussian estimator is shown in Figure 13a. Figure 13b shows the transfer entropy obtained along causal map edges.…”
Section: Tennessee Eastman Processmentioning
confidence: 99%
“…Considering the fault information in real time data, Ji et al proposed a real time fault diagnosis method based on time delayed mutual information. In their work, both historical data under normal operating conditions and real time data were employed for fault propagation analysis, therefore, the changes in variable correlation when a fault occured could be captured to obtain a more objective root cause diagnosis [213]. More research on fault propagation analysis using several other methods can be found, such as k nearest neighbor for a nonlinear multi-input, single-output process [214], and convergent cross-mapping for capturing nonlinear relationships with a low computational cost [215].…”
Section: Causal Reasoning-based Methodsmentioning
confidence: 99%
“…This can be described directlyin an independent way -based on specific elements of knowledge but can be also described in terms of probabilities distributions (in discrete case or probability density functions (in the continuous case), which are provided by information models of the source of the signals. An introduction and more explained examples and case studies are available in [14], [15], and [16].…”
Section: Introductionmentioning
confidence: 99%